2013
DOI: 10.1007/s00455-013-9474-9
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Dysphagia in Patients with Obstructive Sleep Apnea Syndrome

Abstract: Although previous studies demonstrated that patients with obstructive sleep apnea syndrome (OSAS) may present subclinical manifestations of dysphagia, in not one were different textures and volumes systematically studied. The aim of this study was to analyze the signs and symptoms of oropharyngeal dysphagia using fiberoptic endoscopic evaluation of swallowing (FEES) with boluses of different textures and volumes in a large cohort of patients with OSAS. A total of 72 OSAS patients without symptoms of dysphagia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 20 publications
3
38
1
2
Order By: Relevance
“…Both OSA and dysphagia require adequate muscular tone and coordination, and several studies have found that the presence of OSA can exacerbate dysphagia in some patient populations . OSA was less likely to be present in the patients who had a VFSS as compared to those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Both OSA and dysphagia require adequate muscular tone and coordination, and several studies have found that the presence of OSA can exacerbate dysphagia in some patient populations . OSA was less likely to be present in the patients who had a VFSS as compared to those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative respiratory complications following a T&A are relatively common and have been described to occur more frequently in children of younger age [5], and lower body weight was reported to be a risk factor for these complications [6,7]. Additionally, dysphagia associated with poor pharyngeal muscle weakness is a risk factor for aspiration leading to respiratory complications [8]. Our patient thus had a high risk of respiratory complications.…”
Section: Discussionmentioning
confidence: 81%
“…We did not administer any muscle relaxants for any of our patient's three operations because of the risks of hyperkalemia following succinylcholine in patients with neuromuscular disease and the prolongation effect following the administration of nondepolarizing agents. Case reports of patients with other types of leukodystrophy have shown that rocuronium, vecuronium, and atracurium can be safely used without a prolongation effect [8][9][10]. Thus, if rapid sequence induction and intubation is required in a patient with Krabbe disease, a non-depolarizing muscular agent should be used.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search was performed on the databases Lilacs, PubMed and Scopus, crossing the DeCS/MeSH keywords: "Sleep Apnea, Obstructive" (1), "Speech, Language and Hearing Sciences" (2), "Audiology" (3), "Language" (4), "Voice" (5), "Speech Therapy" (6), "Geriatrics" (7), "Public Health" (8) and "Deglutition Disorders" (9). Aiming at the comprehensive action of Speech-Language Pathology, the following free terms were also employed: Oropharyngeal exercises (10), Occupational Speech-Language Pathology (11), Educational Speech-Language Pathology (12), Neurofunctional Speech-Language Pathology (13).…”
Section: Methodsmentioning
confidence: 99%
“…For example, it may be associated with hearing aspects, such as reduced amplitude of P300 4 , sensorineural hearing loss 5 and auditory processing disorders in children 6 (AUDIOLOGY); signs of swallowing disorder 7,8 (DYSPHAGIA); association with work accidents 9 (OCCUPATIONAL SPEECH-LANGUAGE PATHOLOGY) and learning and memory alterations 10 (EDUCATIONAL SPEECH-LANGUAGE PATHOLOGY). Individuals with OSA present higher risk of cerebrovascular accident 3 (NEUROFUNCTIONAL SPEECH-LANGUAGE PATHOLOGY), and OSA is more frequent with aging 11 (GERONTOLOGY).…”
Section: Introductionmentioning
confidence: 99%